Turn bridge. - Salit, Mohd Sapuan; Usubamatov, Ryspek; Yahya, Azmi; Ismail, Napsiah; Megat Ahmad, Megat Mohamad Hamdan; Mohd Yusiff, Rosnah; Adam, Nor Mariah (2009)
The present invention relates to collapsible bridge and more particularly to a turn bridge. The turn bridge comprises a bridge and a central support pivotally supporting the bridge. The unique feature about the present invention is that unlike conventional collapsible bridges which are the swing type, the present bridge rotates to open and close the water passage-way. Using the present system, the power consumption for moving the bridge is considerably reduced while opening and closing speeds are significantly increase.